Method for preparing hierarchical porous ceramic based on thermosensitive emulsion in combination with direct-writing printing forming
Through the combination of thermal emulsion and direct writing printing, the problem of difficult to control the mesoporous form and porosity of porous ceramic materials is solved, and the rapid curing and molding of multi-stage porous ceramics is achieved, and product quality and production efficiency are improved.
Patent Information
- Application Number
- CN202411344320.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-09-25
AI Technical Summary
The existing methods of preparing porous ceramic materials cannot accurately control the pore form and porosity, the production cycle is long, the complex structure is difficult to form, and the uneven drying and curing process leads to internal stress and cracks in the blank, affecting production efficiency.
Using a method based on the combination of thermal emulsion and direct-writing printing, the epoxy resin content, curing agent content and temperature during the curing process are adjusted through the cross-linking reaction between epoxy resin and curing agent, and combined with ceramic powder and oxide nanometers The surface modification of the particles forms a controllable thermal curing emulsion, achieving rapid curing and forming of complex shape multi-stage pore ceramics.
It realizes rapid and controllable in-situ curing and forming of multi-stage pore ceramics, reduces cracks and deformation of blanks, shortens curing time, improves product quality and production rate, and can be adjusted in the pore structure and porosity.
Smart Images

Figure CN119118684A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing multi-level porous ceramics based on thermosensitive emulsion combined with direct writing printing molding, belonging to the technical field of porous ceramic materials. Background Art
[0002] Porous ceramics combine porous structures with ceramic materials to form materials with excellent properties such as high temperature resistance, corrosion resistance, high specific surface area, high porosity, low dielectric loss, good electrical insulation, and high specific strength. They are widely used in thermal insulation, catalyst carriers, fluid filtration, and biological scaffolds. However, due to the limitation of pore size, the application of porous materials has certain limitations.
[0003] Traditional methods for preparing porous ceramics include direct foaming, freeze drying, organic impregnation, emulsion, etc. Most of them cannot accurately control the pore morphology and porosity. Although emulsion droplets as templates can adjust the pore morphology and porosity in a relatively easy way, there are still problems such as long production cycle, difficulty in forming complex structures, and excessive waste of raw materials. Direct writing (DIW) is an economical and time-saving additive manufacturing technology based on extrusion molding, which can accurately control the printed structure according to computer-aided design. Combining DIW with the emulsion method can realize the combination of the micron-scale or even nanoscale pore structure generated by the emulsion slurry itself and the millimeter-scale macropores formed by the printing filament path to form a multi-level pore structure, breaking the limitations of single pore size materials and obtaining complex-shaped structural parts that meet the needs of various scenarios.
[0004] At present, DIW paste is usually composed of ceramic powder, deionized water, organic binder, etc., and its curing process mainly depends on the volatile solvent at room temperature or heating drying. The DIW molding mentioned in the literature with the emulsion as the paste is also limited to the subsequent room temperature drying for curing. The solvent evaporation rate is uneven during the drying and curing process, which can easily lead to internal stress and cracks in the blank; and the drying and curing takes a long time, affecting the production efficiency; the drying process depends on the ambient humidity and temperature, which is difficult to control accurately. Therefore, it is necessary to further design a simple, efficient and controllable curing ceramic slurry that can be used for DIW printing and realize the rapid curing and molding of complex-shaped blanks, greatly improving the production rate while customized production.
[0005] After forming, the emulsion method generally needs to go through a long drying and curing process, and during this process, the green body is only supported by the van der Waals force between the raw material powders, and the strength is relatively low. In order to speed up the curing speed of the emulsion, light curing, microwave curing, ultrasonic assisted curing, thermal curing and other methods are often used in existing research. Compared with other curing methods, thermal curing is suitable for a variety of emulsion systems, the equipment requirements are relatively simple, the temperature and reaction conditions are easy to control, the uniformity is high, the reaction is controllable, and large-scale production can be achieved.
[0006] Among the existing patents related to thermal curing of emulsions, Chinese invention patent CN105153353A prepares an acrylic emulsion for stretching the surface of polyester film. The emulsion preparation cycle is long and the resource consumption is large. The three-dimensional network structure is introduced by different types of acrylic monomers in the emulsion state, and the system does not contain a curing agent. Only when the coating liquid is prepared can the hydroxyl groups in the acrylic emulsion react with the curing agent to further increase the spatial network structure. At the same time, the emulsifier used to stabilize the resin and the aqueous phase also participates in the curing and cross-linking reaction, and there are too many parameters that affect the curing of the emulsion. The emulsion preparation process of this invention does not involve the addition of ceramic particles, and the resin, as part of the final product, is involved in the surface coating application of the polyester film.
[0007] Chinese invention patent CN104877302A prepares a water-based epoxy-modified phenolic resin emulsion for the preparation of adhesives. The main body of the emulsion of this invention is still phenolic resin. The main function of epoxy resin is to modify phenolic resin and increase the bonding performance of the emulsion, and it is not used as a continuous phase to regulate the pore structure. Co-solvents are used to improve the solubility and compatibility of different resins in the system. They are non-volatile and remain in the emulsion, affecting the further processing of the emulsion. Similar to Chinese invention patent CN105153353A, the emulsion system does not contain a curing agent, and curing depends on the subsequent addition of a curing agent. The hydroxyl groups in pentaerythritol triacrylate undergo a cross-linking reaction with the curing agent to form a three-dimensional network structure. The emulsion preparation process does not involve the addition of ceramic particles, and the resin, as part of the final product, participates in the preparation of the adhesive. In summary, the thermal curing of the emulsion does not currently involve the addition of ceramic particles, and is ultimately not used in the preparation of ceramic materials.
[0008] In the existing thermal curing methods for preparing organic solvent-based slurries of ceramics, the curing time of the alkali-excited self-heating curing mentioned in Chinese invention patents CN108285320A and CN108285321A is usually controlled by the alkali-excited reaction rate, and it is difficult to flexibly adjust the curing time and curing temperature. The microwave heating method for rapid curing of slurry proposed in Chinese invention patent CN110713387A has high equipment cost and complexity, and limited penetration depth. The above method does not contain an emulsion template in the slurry, and cannot achieve the preparation of porous ceramics. No thermosetting resin is used, and the curing agent is a metal salt or ester pH regulator that can release high-valent counterions. Summary of the invention
[0009] In view of the difficulty in preparing multi-level porous ceramics with complex shapes, the present invention proposes a method for preparing multi-level porous ceramics based on a heat-sensitive emulsion combined with direct writing printing. The present invention utilizes the heat-curing cross-linking reaction between epoxy resin and curing agent, and effectively controls the curing process by adjusting parameters such as epoxy resin content, curing agent content, and curing temperature; at the same time, by modifying the surface of ceramic powder and / or ceramic powder oxide sol nanoparticles, the second phase is uniformly introduced to obtain a stable, heat-curable emulsion. The heat-curable emulsion is then used as a feed for DIW molding to achieve rapid curing molding of multi-level porous ceramics with complex shapes.
[0010] During the preparation of the emulsion, the amphiphilic particles modified by the surfactant and having a suitable contact angle are irreversibly adsorbed at the oil-water interface. Due to the limited polymerization, an emulsion with controllable droplet size can be formed. Since the emulsion contains epoxy resin and curing agent, when heated, the epoxy groups in the epoxy resin react with the functional groups such as active hydrogen, amine, and anhydride in the curing agent to form a three-dimensional network structure, thereby achieving controllable thermal curing. The second phase (aqueous phase) added to the emulsion evaporates during the curing process, forming the pore structure of the blank in situ. In addition, in the subsequent degreasing and sintering process, organic matter such as epoxy resin is removed and holes are left. In addition, the DIW forming wire column path is used to construct millimeter-level macropores, and finally a multi-level porous structure ceramic is formed.
[0011] The specific technical solutions are as follows:
[0012] The invention provides a thermal emulsion for direct writing printing, wherein the thermal emulsion for direct writing printing comprises a ceramic suspension, deionized water, a surfactant and a curing agent;
[0013] The ceramic suspension comprises ceramic powder and / or ceramic powder oxide sol nanoparticles, epoxy resin and diluent;
[0014] The above-mentioned diluents include active diluents and inert diluents.
[0015] Optionally, the epoxy resin accounts for 5-55 wt.% of the ceramic suspension; the diluent accounts for 5-50 wt.% of the ceramic suspension, wherein the mass ratio of the active diluent to the inert diluent is 1:(0.1-10); in addition to the epoxy resin and the diluent, the ceramic suspension is supplemented by ceramic powder and / or ceramic powder oxide sol nanoparticles to 100 wt.%, and the solid content of the ceramic suspension is 5-85 wt.%;
[0016] The surfactant accounts for 0.2-20.0 wt.% of the mass of the ceramic powder and / or ceramic powder oxide sol nanoparticles;
[0017] The deionized water accounts for 5-200 wt.% of the total mass of epoxy resin and diluent
[0018] The curing agent in the emulsion accounts for 1-50 wt.% of the epoxy resin.
[0019] Optionally, the ceramic powder is one or a mixture of two or more of aluminum oxide, silicon oxide, zirconium oxide, cerium oxide, titanium dioxide, hydroxyapatite, β-tricalcium phosphate, silicon nitride, silicon carbide, fly ash, secondary aluminum ash, coal gangue, kaolin, tailings, and metallurgical slag;
[0020] The ceramic powder oxide sol nanoparticles are one or a mixture of two or more of aluminum sol, silicon sol, zirconium sol, titanium sol and cerium sol.
[0021] Optionally, the epoxy resin is a glycidyl ether epoxy resin, a glycidyl amine epoxy resin or an alicyclic epoxy resin.
[0022] Optionally, the reactive diluent is one or a mixture of two or more of methyl methacrylate, ethylene glycol acrylate, ethylene glycol, butanediol, ethylene glycol methyl ether, ethylene glycol ethyl ether, 1,4-cyclohexanedimethanol diglycidyl ether, and 1,6-hexanediol diglycidyl ether;
[0023] The inert diluent is one or a mixture of two or more of xylene, trimethylbenzene, ethylbenzene, propylene glycol butyl ether, n-butanol, acetone, butyl butyrate and butyl propionate.
[0024] Optionally, the surfactant is one or a mixture of two or more of hyperdispersant 41000, triethanolamine dodecyl sulfate, sodium dodecyl sulfate, sodium α-olefin sulfonate, cocamidopropyl betaine, hexadecyltrimethylammonium chloride, ethylene glycol, glycerol, Tween series, and polyglycerol.
[0025] Optionally, the curing agent is one or a mixture of two or more of water-based polyamide curing agent, triethylenetetramine, water-based isocyanic anhydride curing agent, propylene oxide carboxylate, diethylenediamine, diisopropylamine, polyetheramine, 4,4'-diaminediphenyl ether, 3,3'-diaminexylene, polyethyleneimine, 3,3'-diaminodipropylamine, and dipropylenetriamine.
[0026] If the ceramic powder, ceramic powder oxide sol nanoparticles, epoxy resin, active diluent, inert diluent, surfactant and curing agent mentioned above are a mixture of two or more of the specific substances listed above, the ratio of the mixture can be any ratio.
[0027] The present invention also provides a method for preparing a thermal-sensitive emulsion for direct writing printing, the method comprising the following steps:
[0028] Step 1, adding ceramic powder and / or ceramic powder oxide sol nanoparticles to a solution consisting of epoxy resin and a diluent, and mixing by ball milling to obtain a uniform ceramic suspension;
[0029] Step 2, adding deionized water, a surfactant and a curing agent to the ceramic suspension obtained in step 1, and fully mechanically stirring to obtain a uniform and stable emulsion. The purpose of this step is to use a surfactant to activate the ceramic powder and / or ceramic powder oxide sol nanoparticles described in step 1, and add a curing agent for epoxy resin curing to the system.
[0030] Wherein, the ball milling time in step 1 is 5 min – 48 h; and the mechanical stirring conditions in step 2 are 300 – 3000 rpm, 5 min – 12 h.
[0031] A method for forming multi-level porous ceramics by direct printing of the thermal emulsion according to claim 7, characterized in that it comprises the following steps:
[0032] Step 1, using a thermosensitive emulsion as a direct writing printing paste to directly write a multi-level porous ceramic blank;
[0033] Step 2, subjecting the green blank obtained in step 1 to thermal curing, degreasing and sintering steps to obtain multi-level porous ceramics.
[0034] Optionally, the process parameters of the direct writing printing in step 1 are: printing speed 0.01 – 600 mm / s, nozzle inner diameter 0.1 – 3.6 mm, layer height 0.05 – 3.6 mm;
[0035] The heat curing temperature in step 2 is 25-150°C, and the processing time is 5 min - 15 h; the heating rate during the debinding process is 0.02 - 20°C / min, the debinding temperature is 150 - 1300°C, and the holding time is 5 min - 12 h; the heating rate during the sintering process is 0.1 - 20°C / min, the sintering temperature is 600 - 2000°C, and the holding time is 30 min - 12 h.
[0036] Compared with the prior art, the technical solution provided by the present invention has the following beneficial effects:
[0037] The present invention provides a novel paste for DIW that can be rapidly heat-cured after molding, and the paste contains emulsion droplets as a scaffold-derived hole template, and the rapid and controllable in-situ curing molding of the green body is achieved by optimizing the DIW curing method, and a multi-level porous structure ceramic assembled with micron-level / nano-level and millimeter-level pore structures is obtained, which reduces the generation of defects such as green body cracks and deformations, greatly shortens the curing and drying time after molding, effectively controls the stress distribution during the curing process, and improves the quality and production rate of the multi-level porous ceramic. And the parameters such as the pore structure and porosity can be conveniently regulated by adjusting factors such as the solid content, the oil-water ratio, the degree of hydrophobization of the particle surface, and the content of organic additives.
[0038] The method for forming multi-level porous ceramics by combining a thermosensitive emulsion with direct writing printing described in the present invention has a simple process and low cost, and multi-level porous ceramics with complex shapes can be prepared without a mold, so as to integrate the performance advantages of different pore structures, so that the sample has the advantages of good transmittance, high specific strength, large specific surface area, etc., and has broad application prospects in the fields of thermal insulation filtration, catalyst carriers, biomedical materials, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0040] Figure 1 This is the SEM image of the multi-level porous alumina green body bracket prepared in Example 1.
[0041] Figure 2 This is the SEM image of the multi-level porous alumina ceramic bracket prepared in Example 1.
[0042] Figure 3 This is the SEM image of the alumina green body bracket prepared in Comparative Example 1.
[0043] Figure 4 This is the SEM image of the alumina green body bracket prepared in Comparative Example 2.
[0044] Figure 5 Comparative photos of the emulsions prepared in Comparative Example 3 and Example 1 and SEM images of the alumina green body support: (a) Photo of the emulsion prepared in Example 1; (b) Photo of the emulsion prepared in Comparative Example 3; (c) SEM image of the green body support.
[0045] Figure 6 This is the SEM image of the alumina green body bracket prepared in Comparative Example 4. DETAILED DESCRIPTION
[0046] In order to make the invention purpose, technical scheme and beneficial technical effect of the present invention clearer, the present invention is described in detail below in conjunction with specific embodiments. It should be understood that the embodiments described in this specification are only for explaining the present invention, not for limiting the present invention.
[0047] A thermal emulsion for direct writing printing, the thermal emulsion for direct writing printing comprising a ceramic suspension, deionized water, a surfactant and a curing agent;
[0048] The ceramic suspension comprises ceramic powder and / or ceramic powder oxide sol nanoparticles, epoxy resin and diluent;
[0049] The above-mentioned diluents include active diluents and inert diluents.
[0050] Optionally, the epoxy resin accounts for 5-55 wt.% of the ceramic suspension; the diluent accounts for 5-50 wt.% of the ceramic suspension, wherein the mass ratio of the active diluent to the inert diluent is 1:(0.1-10); in addition to the epoxy resin and the diluent, the ceramic suspension is supplemented by ceramic powder and / or ceramic powder oxide sol nanoparticles to 100 wt.%, and the solid content of the ceramic suspension is 5-85 wt.%.
[0051] If the total content of the diluent is not within the above process parameter range, the emulsion viscosity will be inappropriate and a uniform and regular pore structure will not be formed.
[0052] If the solid content of the ceramic suspension is not within the above process parameter range, the desired pore structure cannot be formed.
[0053] The surfactant accounts for 0.2-20.0 wt.% of the mass of the ceramic powder and / or ceramic powder oxide sol nanoparticles. If the surfactant content is not within the above process parameter range, the emulsion will be unstable, the water phase therein will precipitate, and the pore structure cannot be formed.
[0054] The deionized water accounts for 5-200 wt.% of the total mass of the epoxy resin and the diluent. If the amount of deionized water is not within the above process parameter range, the proportion of the second phase will not meet the conditions required for the technical effect of the present invention, and the pore structure cannot be formed.
[0055] The curing agent in the emulsion accounts for 1-50 wt.% of the epoxy resin.
[0056] Optionally, the ceramic powder is one or a mixture of two or more of aluminum oxide, silicon oxide, zirconium oxide, cerium oxide, titanium dioxide, hydroxyapatite, β-tricalcium phosphate, silicon nitride, silicon carbide, fly ash, secondary aluminum ash, coal gangue, kaolin, tailings, and metallurgical slag;
[0057] The ceramic powder oxide sol nanoparticles are one or a mixture of two or more of aluminum sol, silicon sol, zirconium sol, titanium sol and cerium sol.
[0058] Optionally, the epoxy resin is a glycidyl ether epoxy resin, a glycidyl amine epoxy resin or an alicyclic epoxy resin.
[0059] Optionally, the reactive diluent is one or a mixture of two or more of methyl methacrylate, ethylene glycol acrylate, ethylene glycol, butanediol, ethylene glycol methyl ether, ethylene glycol ethyl ether, 1,4-cyclohexanedimethanol diglycidyl ether, and 1,6-hexanediol diglycidyl ether;
[0060] The inert diluent is one or a mixture of two or more of xylene, trimethylbenzene, ethylbenzene, propylene glycol butyl ether, n-butanol, acetone, butyl butyrate and butyl propionate.
[0061] Optionally, the surfactant is one or a mixture of two or more of hyperdispersant 41000, triethanolamine dodecyl sulfate, sodium dodecyl sulfate, sodium α-olefin sulfonate, cocamidopropyl betaine, hexadecyltrimethylammonium chloride, ethylene glycol, glycerol, Tween series, and polyglycerol.
[0062] Optionally, the curing agent is one or a mixture of two or more of water-based polyamide curing agent, triethylenetetramine, water-based isocyanic anhydride curing agent, propylene oxide carboxylate, diethylenediamine, diisopropylamine, polyetheramine, 4,4'-diaminediphenyl ether, 3,3'-diaminexylene, polyethyleneimine, 3,3'-diaminodipropylamine, and dipropylenetriamine.
[0063] The present invention also provides a method for preparing a thermal-sensitive emulsion for direct writing printing, the method comprising the following steps:
[0064] Step 1, adding ceramic powder and / or ceramic powder oxide sol nanoparticles to a solution consisting of epoxy resin and a diluent, and mixing by ball milling to obtain a uniform ceramic suspension;
[0065] Step 2: Add a surfactant, deionized water and a curing agent to the ceramic suspension obtained in step 1, and stir mechanically to obtain a uniform and stable emulsion.
[0066] Wherein, the ball milling time in step 1 is 5 min – 48 h; and the mechanical stirring conditions in step 2 are 300 – 3000 rpm, 5 min – 12 h.
[0067] A method for forming multi-level porous ceramics by direct printing of the thermal emulsion according to claim 7, characterized in that it comprises the following steps:
[0068] Step 1, using a thermosensitive emulsion as a direct writing printing paste to directly write a multi-level porous ceramic blank;
[0069] Step 2, subjecting the green blank obtained in step 1 to thermal curing, degreasing and sintering steps to obtain multi-level porous ceramics.
[0070] Optionally, the process parameters of the direct writing printing in step 1 are: printing speed 0.01 – 600 mm / s, nozzle inner diameter 0.1 – 3.6 mm, layer height 0.05 – 3.6 mm;
[0071] The heat curing temperature in step 2 is 25-150°C, and the processing time is 5 min - 15 h; the heating rate during the debinding process is 0.02 - 20°C / min, the debinding temperature is 150 - 1300°C, and the holding time is 5 min - 12 h; the heating rate during the sintering process is 0.1 - 20°C / min, the sintering temperature is 600 - 2000°C, and the holding time is 30 min - 12 h.
[0072] Example 1
[0073] (1) Alumina powder was added as the initial raw material to a solution of bisphenol A epoxy resin E-51, butanediol, and xylene, and a uniform ceramic suspension was prepared by ball milling for 12 h. The solid content of the ceramic suspension was 60 wt.%, the epoxy resin accounted for 35 wt.%, the butanediol accounted for 1 wt.%, and the xylene accounted for 4 wt.%.
[0074] (2) A certain amount of triethanolamine dodecyl sulfate, deionized water and triethylenetetramine were added to the ceramic suspension obtained above, and the mixture was stirred mechanically at 2500 rpm for 1 h to obtain a stable particle-stabilized emulsion. The surfactant triethanolamine dodecyl sulfate in the emulsion accounted for 20 wt.% of the powder mass, deionized water as the second phase accounted for 50 wt.% of the total mass of the epoxy resin and the diluent, and the curing agent triethylenetetramine accounted for 20 wt.% of the epoxy resin.
[0075] (3) The emulsion obtained above was used as a paste for direct writing printing. Under the conditions of a printing speed of 5 mm / s, a nozzle inner diameter of 2.1 mm, and a layer height of 2.1 mm, a green blank with a complex structure was printed. The green blank was thermally cured at 80 °C for 2 h, heated to 700 °C at a heating rate of 0.5 °C / min and kept warm for 1 h for degreasing. The green blank was then heated to 1500 °C at a heating rate of 1 °C / min and kept warm for 3 h to obtain a multi-level porous alumina ceramic.
[0076] Example 2
[0077] (1) Aluminum sol powder was added as the initial raw material to a solution of epoxysorbitol glycidyl ether, 1,4-cyclohexanedimethanol diglycidyl ether, and acetone, and then ball milled for 12 h to prepare a uniform ceramic suspension. The solid content of the ceramic suspension was 34 wt.%, epoxy resin accounted for 55 wt.%, 1,4-cyclohexanedimethanol diglycidyl ether accounted for 10 wt.%, and acetone accounted for 1 wt.%.
[0078] (2) A certain amount of hyperdispersant 41000, deionized water and polyetheramine were added to the ceramic suspension obtained above, and the mixture was mechanically stirred at 2000 rpm for 40 min to obtain a stable particle-stabilized emulsion. The hyperdispersant 41000 in the emulsion accounted for 0.2 wt.% of the powder mass, deionized water as the second phase accounted for 5 wt.% of the total mass of the epoxy resin and the diluent, and the curing agent polyetheramine accounted for 50 wt.% of the epoxy resin.
[0079] (3) The emulsion obtained above was used as a paste for direct writing printing. Under the conditions of a printing speed of 6 mm / s, a nozzle inner diameter of 2 mm, and a layer height of 2 mm, a green blank with a complex structure was printed. The green blank was thermally cured at 25 °C for 15 h, heated to 150 °C at a heating rate of 0.02 °C / min and kept warm for 12 h for degreasing, and then heated to 1300 °C at a heating rate of 0.1 °C / min and kept warm for 30 min to obtain a multi-level porous alumina ceramic.
[0080] Example 3
[0081] (1) Hydroxyapatite and β-tricalcium phosphate powders were added as initial raw materials into a solution of ethylene glycol diglycidyl ether, ethylene glycol ethyl ether, and ethylbenzene, and then ball milled for 8 h to prepare a uniform ceramic suspension. The solid content of the ceramic suspension was 39 wt.%, epoxy resin accounted for 50 wt.%, ethylene glycol ethyl ether accounted for 1 wt.%, and ethylbenzene accounted for 10 wt.%.
[0082] (2) Add a certain amount of sodium dodecyl sulfate, hyperdispersant 41000, deionized water and polyethyleneimine to the ceramic suspension obtained above, and fully mechanically stir at 1200 rpm for 40 min to obtain a stable particle-stabilized emulsion. Sodium dodecyl sulfate and hyperdispersant 41000 in the emulsion hydrophobically modify the mixed powder, and the addition amount is 10 wt.% of the total mass of the powder. The mass ratio of the two surfactants is sodium dodecyl sulfate: hyperdispersant 41000=2:1. Deionized water as the second phase accounts for 200 wt.% of the total mass of the epoxy resin and the diluent, and the curing agent polyethyleneimine accounts for 12.5 wt.% of the epoxy resin.
[0083] (3) The emulsion obtained above was used as a paste for direct writing printing. Under the conditions of a printing speed of 100 mm / s, a nozzle inner diameter of 1.2 mm, and a layer height of 1.2 mm, a green blank with a complex structure was printed. The green blank was thermally cured at 70 ℃ for 2 h, heated to 1300 ℃ at a heating rate of 1 ℃ / min and kept warm for 5 min for degreasing, and then heated to 1500 ℃ at a heating rate of 2 ℃ / min and kept warm for 3 h to obtain a multi-level porous biphasic calcium phosphate ceramic.
[0084] Example 4
[0085] (1) Silicon nitride powder was added as the initial raw material to a solution of bisphenol A epoxy resin E-44, ethylene glycol acrylate, and n-butanol, and a uniform ceramic suspension was prepared by ball milling for 5 min. The solid content of the ceramic suspension was 5 wt.%, the epoxy resin accounted for 45 wt.%, the ethylene glycol acrylate accounted for 30 wt.%, and the n-butanol accounted for 20 wt.%.
[0086] (2) A certain amount of Tween 80, deionized water and 3,3'-diaminodipropylamine were added to the ceramic suspension obtained above, and the mixture was mechanically stirred at 300 rpm for 5 min to obtain a stable particle-stabilized emulsion. Tween 80 in the emulsion accounted for 10 wt.% of the powder mass, deionized water as the second phase accounted for 50 wt.% of the total mass of the epoxy resin and the diluent, and the curing agent 3,3'-diaminodipropylamine accounted for 1 wt.% of the epoxy resin.
[0087] (3) The emulsion obtained above was used as a paste for direct writing printing. Under the conditions of a printing speed of 600 mm / s, a nozzle inner diameter of 0.1 mm, and a layer height of 0.05 mm, a green blank with a complex structure was printed. The green blank was thermally cured at 150 °C for 5 min, heated to 700 °C at a heating rate of 20 °C / min and kept at this temperature for 1 h for degreasing, and then heated to 2000 °C at a heating rate of 20 °C / min and kept at this temperature for 2 h to obtain a multi-level porous silicon nitride ceramic.
[0088] Example 5
[0089] (1) Fly ash and secondary aluminum ash powder were added as initial raw materials into a solution of bisphenol F epoxy resin DER 354, 1,6-hexanediol diglycidyl ether, and ethylbenzene, and then ball milled for 48 h to prepare a uniform ceramic suspension. The solid content of the ceramic suspension was 85 wt.%, epoxy resin accounted for 5 wt.%, 1,6-hexanediol diglycidyl ether accounted for 6 wt.%, and ethylbenzene accounted for 4 wt.%.
[0090] (2) A certain amount of propylene glycol, deionized water and diethylenediamine were added to the ceramic suspension obtained above, and the mixture was mechanically stirred at 3000 rpm for 12 h to obtain a stable particle-stabilized emulsion. The propylene glycol in the emulsion accounted for 5 wt.% of the powder mass, the deionized water as the second phase accounted for 70 wt.% of the total mass of the epoxy resin and the diluent, and the curing agent diethylenediamine accounted for 13.8 wt.% of the epoxy resin.
[0091] (3) The emulsion obtained above was used as a paste for direct writing printing. Under the conditions of printing speed of 0.01 mm / s, nozzle inner diameter of 3.6 mm, and layer height of 3.6 mm, a green blank with a complex structure was printed. The green blank was thermally cured at 80 °C for 5 h, heated to 300 °C at a heating rate of 0.5 °C / min and kept at this temperature for 2 h for degreasing, and then heated to 600 °C at a heating rate of 1 °C / min and kept at this temperature for 12 h to obtain a multi-level porous mullite ceramic.
[0092] Comparative Example 1
[0093] (1) Alumina powder was added as the initial raw material to a solution of bisphenol A epoxy resin E-51, butanediol, and xylene, and a uniform ceramic suspension was prepared by ball milling for 12 h. The solid content of the ceramic suspension was 88 wt.%, the epoxy resin accounted for 6 wt.%, the butanediol accounted for 4 wt.%, and the xylene accounted for 2 wt.%.
[0094] (2) A certain amount of triethanolamine dodecyl sulfate, deionized water and triethylenetetramine were added to the ceramic suspension obtained above, and the mixture was mechanically stirred at 1000 rpm for 30 min to obtain a stable particle-stabilized emulsion. The surfactant triethanolamine dodecyl sulfate in the emulsion accounted for 7 wt.% of the powder mass, deionized water as the second phase accounted for 50 wt.% of the total mass of the epoxy resin and the diluent, and the curing agent triethylenetetramine accounted for 20 wt.% of the epoxy resin.
[0095] (3) The emulsion obtained above was used as a paste for direct writing printing, and a green blank with a complex structure was printed under the conditions of a printing speed of 10 mm / s, a nozzle inner diameter of 1.5 mm, and a layer height of 1.5 mm. The SEM image of the green blank scaffold (see Appendix) Figure 3 ), when the solid content exceeds the parameter range of 5-85 wt.% specified in the present invention, there is no porous structure, and the preparation of the multi-level porous ceramic material with the technical effect described in the present invention cannot be achieved.
[0096] Comparative Example 2
[0097] (1) Alumina powder was added as the initial raw material to a solution of bisphenol A epoxy resin E-51, butanediol, and xylene, and a uniform ceramic suspension was prepared by ball milling for 12 h. The solid content of the ceramic suspension was 60 wt.%, the epoxy resin accounted for 37 wt.%, the butanediol accounted for 2 wt.%, and the xylene accounted for 1 wt.%.
[0098] (2) A certain amount of triethanolamine dodecyl sulfate, deionized water and triethylenetetramine were added to the ceramic suspension obtained above, and the mixture was mechanically stirred at 1000 rpm for 30 min to obtain a stable particle-stabilized emulsion. The surfactant triethanolamine dodecyl sulfate in the emulsion accounted for 7 wt.% of the powder mass, deionized water as the second phase accounted for 50 wt.% of the total mass of the epoxy resin and the diluent, and the curing agent triethylenetetramine accounted for 20 wt.% of the epoxy resin.
[0099] (3) The emulsion obtained above was used as a paste for direct writing printing, and a green blank with a complex structure was printed under the conditions of a printing speed of 10 mm / s, a nozzle inner diameter of 1.5 mm, and a layer height of 1.5 mm. The SEM image of the green blank scaffold (see Appendix) Figure 4 ), when the total content of the diluent is less than the parameter range of 5-50 wt.% specified in the present invention, the viscosity of the emulsion is too large, the pore structure is uneven and irregular, and the preparation of the multi-level porous ceramic material with the technical effect of the present invention cannot be achieved.
[0100] Comparative Example 3
[0101] (1) Aluminum sol powder was added as the initial raw material to a solution of epoxysorbitol glycidyl ether, 1,4-cyclohexanedimethanol diglycidyl ether, and acetone, and then ball milled for 12 h to prepare a uniform ceramic suspension. The solid content of the ceramic suspension was 30 wt.%, epoxy resin accounted for 35 wt.%, 1,4-cyclohexanedimethanol diglycidyl ether accounted for 23.33 wt.%, and acetone accounted for 11.67 wt.%.
[0102] (2) A certain amount of hyperdispersant 41000, deionized water and polyetheramine were added to the ceramic suspension obtained above, and the mixture was mechanically stirred at 2000 rpm for 40 min to obtain an emulsion. The hyperdispersant 41000 in the emulsion accounted for 30 wt.% of the powder mass, the deionized water as the second phase accounted for 20 wt.% of the total mass of the epoxy resin and the diluent, and the curing agent polyetheramine accounted for 33.33 wt.% of the epoxy resin.
[0103] (3) The obtained emulsion was used as a paste for direct writing printing, and a green blank with a complex structure was printed under the conditions of a printing speed of 6 mm / s, a nozzle inner diameter of 2 mm, and a layer height of 2 mm. When the surfactant content exceeded the parameter range of 0.2-20.0 wt.% of the powder mass specified in the present invention, the emulsion was unstable and the water phase precipitated (attached Figure 5 ). The SEM image of the green body bracket shows a non-porous structure, and the preparation of the multi-level porous ceramic material with the technical effect described in the present invention cannot be achieved.
[0104] Comparative Example 4
[0105] (1) Aluminum sol powder was added as the initial raw material to a solution of epoxysorbitol glycidyl ether, 1,4-cyclohexanedimethanol diglycidyl ether, and acetone, and then ball milled for 12 h to prepare a uniform ceramic suspension. The solid content of the ceramic suspension was 30 wt.%, epoxy resin accounted for 35 wt.%, 1,4-cyclohexanedimethanol diglycidyl ether accounted for 23.33 wt.%, and acetone accounted for 11.67 wt.%.
[0106] (2) A certain amount of hyperdispersant 41000, deionized water and polyetheramine were added to the ceramic suspension obtained above, and the mixture was mechanically stirred at 2000 rpm for 40 min to obtain a stable particle-stabilized emulsion. The hyperdispersant 41000 in the emulsion accounted for 7.5 wt.% of the powder mass, deionized water as the second phase accounted for 2 wt.% of the total mass of the epoxy resin and the diluent, and the curing agent polyetheramine accounted for 33.33 wt.% of the epoxy resin.
[0107] (3) The emulsion obtained above was used as a paste for direct writing printing. Under the conditions of printing speed of 6 mm / s, nozzle inner diameter of 2 mm, and layer height of 2 mm, a green blank with a complex structure was printed. The SEM image of the green blank support (see Appendix) Figure 6 ), when the deionized water is less than the parameter range of 5-200 wt.% of the total mass of the epoxy resin and the diluent specified in the present invention, the proportion of the second phase is too low, there is no porous structure, and the preparation of the multi-level porous ceramic material with the technical effect of the present invention cannot be achieved.
[0108] In summary, the comparative examples and attached Figure 3-6 It can be seen that if the key process conditions (solid content, diluent, surfactant, deionized water) are not within the protection scope of the present invention, the multi-level porous ceramic material cannot be successfully prepared.
[0109] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can easily think of various equivalent modifications or substitutions within the technical scope disclosed by the present invention, and these modifications or substitutions should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope determined by the claims.
Claims
1. A thermal emulsion for direct writing printing, characterized in that: The direct-write printing thermal emulsion comprises a ceramic suspension, a curing agent, deionized water and a surfactant; The ceramic suspension comprises ceramic powder and / or ceramic powder oxide sol nanoparticles, epoxy resin and diluent; The above-mentioned diluents include active diluents and inert diluents.
2. The thermal emulsion for direct writing printing according to claim 1, characterized in that: The epoxy resin accounts for 5-55 wt.% of the ceramic suspension; the diluent accounts for 5-50 wt.% of the ceramic suspension, wherein the mass ratio of the active diluent to the inert diluent is 1:(0.1-10); in addition to the epoxy resin and the diluent, the ceramic suspension is supplemented by ceramic powder and / or ceramic powder oxide sol nanoparticles to 100 wt.%, and the solid content of the ceramic suspension is 5-85 wt.%; The surfactant accounts for 0.2-20.0 wt.% of the mass of the ceramic powder and / or ceramic powder oxide sol nanoparticles; The deionized water accounts for 5-200 wt.% of the total mass of epoxy resin and diluent The curing agent in the emulsion accounts for 1-50 wt.% of the epoxy resin.
3. A thermal-sensitive emulsion for direct writing printing according to claim 2, characterized in that: The ceramic powder is one or a mixture of two or more of aluminum oxide, silicon oxide, zirconium oxide, cerium oxide, titanium dioxide, hydroxyapatite, β-tricalcium phosphate, silicon nitride, silicon carbide, fly ash, secondary aluminum ash, coal gangue, kaolin, tailings, and metallurgical slag; The ceramic powder oxide sol nanoparticles are one or a mixture of two or more of aluminum sol, silicon sol, zirconium sol, titanium sol and cerium sol.
4. The thermal-sensitive emulsion for direct writing printing according to claim 3, characterized in that: The epoxy resin is a glycidyl ether epoxy resin, a glycidyl amine epoxy resin or an alicyclic epoxy resin.
5. The thermal-sensitive emulsion for direct writing printing according to claim 4, characterized in that: The active diluent is one or a mixture of two or more of methyl methacrylate, ethylene glycol acrylate, ethylene glycol, butanediol, ethylene glycol methyl ether, ethylene glycol ethyl ether, 1,4-cyclohexanedimethanol diglycidyl ether, and 1,6-hexanediol diglycidyl ether; The inert diluent is one or a mixture of two or more of xylene, trimethylbenzene, ethylbenzene, propylene glycol butyl ether, n-butanol, acetone, butyl butyrate and butyl propionate.
6. The thermal emulsion for direct writing printing according to claim 5, characterized in that: The surfactant is one or a mixture of two or more of hyperdispersant 41000, triethanolamine dodecyl sulfate, sodium dodecyl sulfate, sodium α-olefin sulfonate, cocamidopropyl betaine, hexadecyltrimethylammonium chloride, ethylene glycol, glycerol, Tween series, and polyglycerol.
7. The thermal emulsion for direct writing printing according to claim 6, characterized in that: The curing agent is one or a mixture of two or more of water-based polyamide curing agent, triethylenetetramine, water-based isocyanic anhydride curing agent, propylene oxide carboxylate, diethylenediamine, diisopropylamine, polyetheramine, 4,4'-diaminediphenyl ether, 3,3'-diaminexylene, polyethyleneimine, 3,3'-diaminodipropylamine, and dipropylenetriamine.
8. A method for preparing the thermal-sensitive emulsion for direct writing printing according to any one of claims 1 to 7, characterized in that: The steps include: Step 1, adding ceramic powder and / or ceramic powder oxide sol nanoparticles to a solution consisting of epoxy resin and a diluent, and mixing by ball milling to obtain a uniform ceramic suspension; Step 2, adding a surfactant, deionized water and a curing agent to the ceramic suspension obtained in step 1, and fully mechanically stirring to obtain a uniform and stable emulsion; Wherein, the ball milling time in step 1 is 5 min – 48 h; and the mechanical stirring conditions in step 2 are 300 – 3000 rpm, 5 min – 12 h.
9. A method for forming multi-level porous ceramics by direct printing using the thermosensitive emulsion according to any one of claims 1 to 7, characterized in that: The steps include: Step 1, using a thermosensitive emulsion as a direct writing printing paste to directly write a multi-level porous ceramic blank; Step 2, subjecting the green blank obtained in step 1 to thermal curing, degreasing and sintering steps to obtain multi-level porous ceramics.
10. The method for directly printing and forming multi-level porous ceramics according to claim 9, characterized in that: The process parameters of direct writing printing described in step 1 are: printing speed 0.01 – 600 mm / s, nozzle inner diameter 0.1 – 3.6 mm, layer height 0.05 – 3.6 mm; The heat curing temperature in step 2 is 25-150°C, and the processing time is 5 min - 15 h; the heating rate during the debinding process is 0.02 - 20°C / min, the debinding temperature is 150 - 1300°C, and the holding time is 5 min - 12 h; the heating rate during the sintering process is 0.1 - 20°C / min, the sintering temperature is 600 - 2000°C, and the holding time is 30 min - 12 h.
Citation Information
Patent Citations
Waterborne epoxy modified phenolic resin emulsion, preparation method thereof and adhesive prepared by using same as raw material
CN104877302A
Acrylate emulsion as well as preparation method and application thereof
CN105153353A
Self-heating curing ceramic slurry used for 3D printing and preparation method thereof
CN108285320A
3D printing ceramic based on self-heating curing technology and preparation method thereof
CN108285321A
Direct solidification injection molding method for rapidly curing ceramic slurry through microwave heating
CN110713387A
Cited By
Stretchable mechanical metamaterial composite membrane based on direct writing printing and preparation method and application thereof
CN120795382A
Method for preparing porous ceramic through gel casting of emulsion
CN120943649A
